PENGARUH LATIHAN DRIBBLE SLALOM TERHADAP KETERAMPILAN DRIBBLING PEMAIN SSB MUDA MANDIRI U-15 PEKANBARU - Wijayanti, Ni Putu Nita; ', Nasdaldi; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this study was to determine the effects of dribbling slalom exercise on the dribbling skills SSB Muda Mandiri players U-15 Pekanbaru. The study used the kind of approach one-group pretest-posttest design. The population in this study are all players SSB Muda Mandiri U-15 Pekanbaru, amounting to 18 people. Data collection techniques used is a full sampling is sampling when all members of the population used as a sample. Test were analyzed using statistical t-test. the results of the analysis showed that there is a slalom dribble exercise influence on the player dribbling skills SSB Muda Mandiri U-15 Pekanbaru, from an average of 20.33 on initial tests be 22.26 on the final test. With a mean difference (thitung 5.049 and 1.753 ttabel).Keywords : Dribble Slalom Exercise, Football